KEPEMILIKAN INSTITUSIONAL DAN KONFLIK KEAGENAN DI PASAR MODAL INDONESIA - Teguh Prasetyo (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
This research aims to test the agency theory in Indonesian capitalmarket was proxied by the variable mechanism controlling the agencyconflicts, based on institutional ownership. The data used in this studyis secondary data drawn from the Osiris database, ICMD. It is industrial company, excepted insurance companies and financialservices that meet the criterian sampling and it was listed on theIndonesia Stock Exchange (BEI). The data is in the form of pooleddata with the observation period from the year 2004-2010. Variablesused in this study is that the company's performance to theperformance of utility assets and Tobin's q accounting for marketperformance as a proxy for agency conflicts as well as the dependentvariable. As for institutional ownership as independent variables andfirm size as a control variable. The method of analysis used in thisstudy is multiple regression of pooled data analysis. The results of thisstudy is an institutional ownership has a positive effect onperformance. That is, institutional ownership having character tocontrol the agency conflict. With the result that, institutionalownership has been play function of binding and oversight of agencyconflict.